Impaired Reactive Stepping Among Patients Ready for Discharge From Inpatient Stroke Rehabilitation. Issue 12 (1st December 2014) - Inness, Elizabeth L.; Mansfield, Avril; Lakhani, Bimal; Bayley, Mark; McIlroy, William E.
Abstract : Background: Individuals with stroke are at increased risk for falls soon after hospital discharge. The ability to react to a balance perturbation, specifically with a rapid step, is critical to maintain balance and prevent falls. Objective: The purpose of the study was to determine the prevalence of impaired reactive stepping responses in an ambulatory group of patients with stroke who were preparing for discharge from inpatient rehabilitation and the relationship to patient performance on commonly used clinical measures of balance, mobility, and lower limb impairment. Design: This study was a retrospective analysis of patient admissions over a 3-year period. Methods: Charts were reviewed for patients who, at time of discharge, had completed a perturbation-evoked reactive stepping assessment. Results: Ninety-nine (71%) of 139 patients had impaired stepping reactions characterized by the need for assistance, an inability to step with either lower limb, or the need for multiple-step responses. There was a statistically significant difference in clinical scores between those with and without impaired stepping, but groups were characterized by considerable variation in clinical profiles. For example, Berg Balance Scale scores ranged from 25 to 55 versus 20 to 56 and gait speeds ranged from 0.17 to 1.43 versus 0.26 to 1.55 m/s for patients who demonstrated a failed step versus a successful step, respectively. Limitations: Not all patients who attended stroke rehabilitation received a reactive stepping assessment at discharge. Conclusions: Impaired reactive stepping is a prevalent problem for ambulatory patients with stroke preparing for discharge, possibly increasing their risk of falling when faced with the challenges of community ambulation. Specific tests that target the capacity to perform perturbation-evoked stepping reactions may be important to identify those at risk for falls and to direct appropriate intervention strategies.